Pelatihan Mendeley Dan Anti-Plagiat Untuk Meningkatkan Kualitas Karya Ilmiah Mahasiswa - Syaikhul Fallah (The Community Engagement Journal, 2019)
The training was carried out aimed at increasing students' willingness to write scientific papers, and improving reference search capabilities in various sources with the Mendeley application. The training is preceded by providing information to students about the training activities that will be carried out. The material presented at the training was: 1) Urgency of writing scientific papers for improving the quality of thesis, 2) Strategies in quoting other people's work, 3) Knowledge of plagiarism and methods of scanning it. After the training, the results obtained were: 1) increasing willingness of teachers to write scientific papers, 2) increasing students' ability to write scientific papers, 3) increasing reference search capabilities at various sources, and 4) participants can know methods to avoid plagiarism.